Fracture strengths and microstructures of Si(3)N(4)/SiC nanocomposites fabricated by in-situ process - Oh, YS; Kim, CS; Lim, DS; Cheong, DS (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
Si(3)N(4)/SiC nanocomposites was prepared by in-situ process using commercial phenolic resin. Microstructures were examined by Transmission Electron Microscopy and Scanning Electron Microscopy. The room and high temperature fracture strengths of Si(3)N(4)/SiC nanocomposites have been studied using the 3-point bending test. The fracture strength of Si(3)N(4)/SiC nanocomposites with Al(2)O(3) and Y(2)O(3) doped samples was about 1100 MPa at room temperature. The fracture strength of Si(3)N(4)/SiC nanocomposites with only Y(2)O(3) doped samples was about 1100 MPa at room temperature and 800 MPa at 1400 degreesC. The grain boundary phases formed during sintering process were examined by X-ray Diffraction method. (C) 2001 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.
Keywords: COMMERCIAL POLYMER; LASER